The Genetic Diversity, Population Structure, and Historical Dynamics of Wild Pyrus Species on the Yunnan–Kweichow Plateau - Xiang Yang; Xingguang Dong; Kunming Li; Ying Zhang; Chenxi Xu; Hongliang Huo; Luming Tian; Jiayu Xu; Chao Liu; Dan Qi; Yufen Cao (Horticulturae)
Located in the southwestern region of China, the Yunnan–Kweichow Plateau, is closely related to the origins of Pyrus L. Despite this important status, there has been relatively little population genetics research focused on the wild Pyrus species in this area. To address this gap in knowledge, the present study was conducted investigating wild Pyrus species distributions in the Yunnan–Kweichow Plateau region. These analyses entailed the collection of 80 accessions, whole-genome resequencing, and the detection of variants including SNPs, InDels, SVs, and CNVs. Genetic structure analyses revealed clear differences between P. pashia and P. calleryana, where the former was additionally subdivided into five groups. The genetic structure of these accessions was closely aligned with their geographic distribution, highlighting the fragmented nature of wild Pyrus populations on the Yunnan–Kweichow Plateau. Analyses of genetic diversity suggested that the central and easter portions of Yunnan Province are key centers of Pyrus diversity on the Yunnan–Kweichow Plateau, whereas the highest degree of differentiation was observed for wild Pyrus in the southwest and northwest regions. Demographic analyses indicated that wild Pyrus populations on the Yunnan–Kweichow Plateau are currently in a state of population contraction, with evidence of migration events between these populations.